Existence of Mild Solutions for a Class of Impulsive Hilfer Fractional Coupled Systems - Karim Guida; Khalid Hilal; Lahcen Ibnelazyz (Advances in Mathematical Physics)
The aim of this paper is to give existence results for a class of coupled systems of fractional integrodifferential equations with Hilfer fractional derivative in Banach spaces. We first give some definitions, namely the Hilfer fractional derivative and the Hausdorff’s measure of noncompactness and the Sadovskii’s fixed point theorem.